Peningkatan keterampilan Menulis Narasi Dengan Menggunakan Model Circuit Learnig Di Kelas Va SD Negeri 23 Marapalam Kota Padang - Oktavia Ningsih, Astuti; Taufik, Taufina; Zainarlis, Zainarlis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the students’ narrative writing skill through the use of the I models in Grade V A of Elementary School Numbern 23 Marapalam, Padang. This is a classroom action research with qualitativeand quantitative approaches. The object of this study is the class teacher and 27 students of Grade V A of Elementary School Number 23 Marapalam, Padang. Student learning outcomes in the cycle I of the prewriting stage were 74,51% increasing in the cycle II to 86,64%. At the time of writing the cycle I 71,33% increased in the cycle II  to 83,25%. In the post-writing stage of the cycle I 70,83% increased in the cycle II  to 86,57%. The results of this study indicate that students’ narrative writing skills increased from the cycle I to obtain an average scre of 72,23% in th cycle II increased to 85,16%. Based on these result, it can be conclude that learning to write narrative using the Circuit Learning model can increase.